A Potential Method for Rapid Screening of Amphioxus Founder Harboring Germline Mutation and Transgene - Zou, Jiaqi; Wu, Xiaotong; Shi, Chenggang; Zhong, Yanhong; Zhang, Lei; Yan, Qiuning; Su, Liuru; Li, Guang (Frontiers in Cell and Developmental Biology, 2021)
Amphioxus is a promising model organism for understanding the origin and evolution of vertebrates due to its basal phylogenetic position among chordates. We here compared the mutation efficacy and mutation type of tail tips and gametes of amphioxus founders injected with Cas9 protein and six different sgRNAs targeting five distinct genes, and revealed a strong correlation for mutation efficacy and a weak correlation for mutation type among the two tissues. In addition, we also observed a positive relationship between gene insertions observed in tail tips and gametes of amphioxus founders injected with Tol2 transposase and two different transgenic constructs. Finally, we showed that amphioxus larvae which had their tail tips cut at the 3-4 gill-slit stage were able to recover within five days and developed a normal number of gonads at the adult stage. Together, these findings indicate a great potential for obtaining valid amphioxus founders with desired mutations and transgenes at as early as the 3 gill-slit larval stage, which will certainly speed up the generation of amphioxus mutants and transgenes and make it more cost- and labor-effective.